Dark Humor, Irony, and the Collaborative Narrativizations of Regional Belonging - Ridanpää, Juha (GeoHumanities, 2019)
In literary geography there is a relatively long history of studying regional narratives, but less focus has been placed on how senses of spatial belonging and identity become actualized through the reception and reinterpretations of regional literatures. This article discusses how Meänkieli-speaking minorities in northern Sweden narrativize their shifting spatial identities through regional literature, specifically Mikael Niemi's successful humorous novel Populärmusik från Vittula (2000). The article approaches the literary work simultaneously through the critical analysis of the book's content, readers' interpretations, and the interconnections between the author, the reader, and wider social circumstances. The analysis is based on group discussions conducted in northern Sweden between September 2015 and February 2016. As an outcome of these discussions, it emerged how different manners of approaching the irony and dark humor of Niemi's book divide people's senses of regional belonging and launch the alternative, confronting conceptions of "who we are."